Correlation between the Severity and Outcome of Acute Calculous Cholecystits According to Tokyo Guidelines - Thapa, Pradip; Adhikari, Krishna Mohan; Sharma, Anup (Journal of Nepalgunj Medical College, 2019)
Introduction: Acute Calculous Cholecystitis is a condition in which the gallbladder becomes inflamed due to cholelithiasis. Early diagnosis, severity grading and appropriate intervention reduce both morbidity and mortality. The aim of this prospective study is to correlate the severity with the outcome of acute calculous cholecystitis according to Tokyo Guidelines. Methods: This was a hospital based prospective study conducted in the Department of Surgery, Nepalgunj Medical College Teaching Hospital for a period of two years from April 2017 to March 2019. The patients were classified into three groups according to the severity grading in the Tokyo guidelines (TG18/ TG13). Clinical characteristics among these patients were analyzed for comparison. Results: Among all diagnostic criteria, right upper quarter (RUQ)h abdominal pain (94%) Murphy’s sign (94%) and thickened gallbladder wall (80%) had the highest sensitivity rates (p<0.032), whereas elevated white cell count (32%) and RUQ abdominal mass (32%) had the lowest sensitivity rates (p<0.035). Higher sensitivity rates of diagnostic criteria were related to severe cholecystitis, except for Fever (46%) and elevated white blood cell (WBC) count (32%). All the 28 patients in grade I and selected patients 3 out of 6in grade II underwent early laparoscopic cholecystectomy (LC) without any conversion and increased morbidity and mortality. Out of16 patients in grade III there was 2 mortalities due to ARDS, 1 needed Ultrasonography (USG) guided cholecystostomy, 1 underwent emergency cholecystectomy. 16 patients, 3 in grade II and 13 in grade III underwent interval laparoscopic cholecystectomy safely. There were no major postoperative morbidities except for superficial surgical site infection (SSI) in 1 patient in grade III who underwent emergency cholecystectomy Higher grade of severity was associated with increased morbidity and mortality (p<0.03). Conclusion: A combination of diagnostic criteria with different path physiologic findings, as noted in the Tokyo guidelines, can help clinicians make the correct diagnosis for patients with acute cholecystitis and there was strong correlation between the severity and outcomes of acute cholecystitis.